2013
DOI: 10.1038/ncomms2776
|View full text |Cite
|
Sign up to set email alerts
|

Efficient room-temperature nuclear spin hyperpolarization of a defect atom in a semiconductor

Abstract: Nuclear spin hyperpolarization is essential to future solid-state quantum computation using nuclear spin qubits and in highly sensitive magnetic resonance imaging. Though efficient dynamic nuclear polarization in semiconductors has been demonstrated at low temperatures for decades, its realization at room temperature is largely lacking. Here we demonstrate that a combined effect of efficient spin-dependent recombination and hyperfine coupling can facilitate strong dynamic nuclear polarization of a defect atom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
50
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 36 publications
1
50
0
8
Order By: Relevance
“…Particularly, the electron spin depolarization in the magnetic field perpendicular to the exciting beam (Hanle effect, the Voigt geometry) is described by a superposition of two Lorentzian contours with widths at half maximum differing by two or three orders: the large spin relaxation time of localized electrons (∼1 ns) determines the width of the narrow contour (∼100 G) whereas the short lifetime of free electrons (∼1 ps) sets the width ∼25 kG of the wide contour [8,9]. Also, it has recently been established [10][11][12][13][14] that the magnetic field directed along the exciting beam (the Faraday geometry) can lead to an increase in the efficiency of spin filter and, as a consequence, to a substantial (up to twice) enhancement of the electron polarization and intensity of the edge photoluminescence (PL) at low and moderate pumping rates. This effect is based on the longitudinal-magnetic-field induced suppression of the electron spin depolarization caused by the hyperfine interaction of a localized electron with the nucleus of the paramagnetic center which localizes this electron.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the electron spin depolarization in the magnetic field perpendicular to the exciting beam (Hanle effect, the Voigt geometry) is described by a superposition of two Lorentzian contours with widths at half maximum differing by two or three orders: the large spin relaxation time of localized electrons (∼1 ns) determines the width of the narrow contour (∼100 G) whereas the short lifetime of free electrons (∼1 ps) sets the width ∼25 kG of the wide contour [8,9]. Also, it has recently been established [10][11][12][13][14] that the magnetic field directed along the exciting beam (the Faraday geometry) can lead to an increase in the efficiency of spin filter and, as a consequence, to a substantial (up to twice) enhancement of the electron polarization and intensity of the edge photoluminescence (PL) at low and moderate pumping rates. This effect is based on the longitudinal-magnetic-field induced suppression of the electron spin depolarization caused by the hyperfine interaction of a localized electron with the nucleus of the paramagnetic center which localizes this electron.…”
Section: Introductionmentioning
confidence: 99%
“…A recent demonstration has shown that nuclear spins proximate to divacancies and related defects in 4H-and 6H-SiC can be effectively polarized [36], an important step towards enabling long-lived quantum-information processing in this technologically mature semiconductor material. The transfer of the point defects' electron spin polarization can also lead to hyperpolarization of the host material, thereby enabling sensitivity-enhanced nuclear magnetic resonance and spintronic applications [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Moreover, strong spin-dependent recombination in these materials mediated by defects allows achieving a record-high electron spin polarization of up to 43% at room temperature (RT), which makes the Ga(In)NAs alloys an ideal materials system for innovative spin filters, spin detectors, amplifiers, and nuclear spin hyperpolarizers operational at RT. [13][14][15][16] Most recently, it was shown that GaNAs can be grown not only in planar but also in NW architecture, i.e., as a shell layer in GaAs/GaNAs core/shell structures. 17,18 This raises the prospect of combining advantages of this materials system with those offered by the one-dimensional (1D) NW architecture.…”
mentioning
confidence: 99%